Target Tracking with NLOS Detection and Mitigation in Wireless Sensor Networks - Xiaoping Wu; Junguo Hu; Yujia Jiang; Enbin Liu; Guoying Wang (International Journal of Distributed Sensor Networks, 2013)
RN and SSR approaches are designed to detect NLOS propagation paths in this paper. When the NLOS propagation paths are detected, an estimation approach for the NLOS range errors is proposed by using residual-error decomposition. The approach can estimate the NLOS range errors quickly and effectively, even if there are multiple NLOS propagation paths. Combining the movement equation with observation position, the position of mobile target node can be tracked precisely with Kalman filter algorithm. Using the estimated NLOS range errors, we correct the localization result and modify Kalman filter to mitigate the NLOS propagations. The simulations demonstrate the validity with RN and SSR detection methods and analyze the impacts of NLOS range errors and number of NLOS anchor nodes. The estimated NLOS range errors are proved to be close to the true especially when the NLOS range errors are much bigger than LOS range errors. The simulation results show that the position of target node can be tracked precisely and effectively, when the NLOS mitigation is used to track the target node position with modified Kalman filter.